Inter-laboratory analysis of cereal beta-glucan extracts of nutritional importance: An evaluation of different methods for determining weight-average molecular weight and molecular weight distribution. (June 2022) - Ballance, Simon; Lu, Yudong; Zobel, Hanne; Rieder, Anne; Knutsen, Svein Halvor; Dinu, Vlad T.; Christensen, Bjørn E.; Ulset, Ann-Sissel; Schmid, Marius; Maina, Ndegwa; Potthast, Antje; Schiehser, Sonja; et al.
Abstract: In an interlaboratory study we compare different methods to determine the weight-average molecular weight ( M w ) and molecular weight distribution of six cereal beta-glucan isolates of nutritional importance. Size-exclusion chromatography (SEC) with multi-angle light scattering (MALS), capillary viscometry, sedimentation velocity analytical ultracentrifugation and one asymmetric flow field-flow fractionation (AF4)-MALS method all yielded similar M w values for mostly individual chains of dissolved beta-glucan molecules. SEC with post-column calcofluor detection underestimated the M w of beta-glucan >500 × 10 3 g/mol. The beta-glucan molecules analysed by these methods were primarily in a random coil conformation as evidenced from individual Mark-Houwink-Kuhn-Sakurada (MHKS) scaling coefficients between 0.5 and 0.6 and Wales-Van Holde ratios between 1.4 and 1.7. In contrast, a second AF4-MALS method yielded much larger M w values for these same samples indicating the presence and detection of beta-glucan aggregates. Storage of the six beta-glucan solutions in the dark at 4 °C for 4 years revealed them to be stable. This suggests an absence of storage-induced irreversible aggregation phenomena or chain-scission. Shear forces in SEC and the viscometer capillary and hydrostatic pressure in analytical ultracentrifugation probably led to the reversable dissociation of beta-glucan aggregates into molecularly dissolved species. Thus, all these methods yield true weight-average molecular weight values not biased by the presence of aggregates as was the case in one of the AF4 based methods employed. Graphical abstract: Image 1 Highlights: Molecular dissolved beta-glucan dominated in six of the methods evaluated. Aggregates of beta-glucan were dominant in only one method evaluated. Abundance of aggregates led to an overestimation of weight-average molecular weight. Aggregates of beta-glucan are disrupted by shear forces and/or hydrostatic pressure. Beta-glucans in solution are stable at 4 °C in the dark for at least four years.